The Evaluation of Space Quality in Outdoor Open Spaces: Bursa Historical Bazaar and Khans District as a Case - Sen, Seyhan; Arslan, Tulin Vural (European Journal of Sustainable Development, 2016)
The evolution of urban life, resulting from the developments in technology, economics and social life, along side with rapid urbanisation has shaped functions and structures of urban outdoor spaces. Together with this change, the expectation of quality has also changed which necessitates the new definitions and parametres about the concept of quality of life. Because the concept of quality consists of various components, the promotion of these definitions and parameters requires taking the specific qualifications of the particular space into consideration. In this study, quality of life and space in Bursa Historical Bazaar and Khans District is evaluated in regard to parameters which are identified in the content of study. These parametres are developed both by the examination of related literature about the space quality and also surveys about the users’ expectations from the site. In in order to identify the users’ expectations from the site, a survey was conducted of 400 people in 4 well-known Khans in the district. The questionnaire items were factor analyzed to explore the principal components of outdoor space quality from the viewpoint of users.